2021
DOI: 10.1016/j.xcrm.2021.100420
|View full text |Cite
|
Sign up to set email alerts
|

Intradermal-delivered DNA vaccine induces durable immunity mediating a reduction in viral load in a rhesus macaque SARS-CoV-2 challenge model

Abstract: Coronavirus disease 2019 (COVID-19), caused by the SARS-CoV-2 virus, has had a dramatic global impact on public health, social, and economic infrastructures. Here, we assess the immunogenicity and anamnestic protective efficacy in rhesus macaques of an intradermal (ID)-delivered SARS-CoV-2 spike DNA vaccine, INO-4800, currently being evaluated in clinical trials. Vaccination with INO-4800 induced T cell responses and induced spike antigen and RBD binding antibodies with ADCP and ADCD activity. Sera from the an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 58 publications
0
20
0
Order By: Relevance
“…8 ZyCoV-D, INO-4800, and pSARS2-S, carrying the SARS-CoV-2 spike gene, induced protective immune responses in animals. [9][10][11] COVID-eVax, encoding secreted monomeric SARS-CoV-2 RBD, induced stronger antibody responses than DNA vaccine candidates encoding full-length S protein and S1 subunit protein. 12 COVID-eVax has been demonstrated to confer mice and ferrets substantial protection against the SARS-CoV-2 challenge.…”
Section: Introductionmentioning
confidence: 98%
“…8 ZyCoV-D, INO-4800, and pSARS2-S, carrying the SARS-CoV-2 spike gene, induced protective immune responses in animals. [9][10][11] COVID-eVax, encoding secreted monomeric SARS-CoV-2 RBD, induced stronger antibody responses than DNA vaccine candidates encoding full-length S protein and S1 subunit protein. 12 COVID-eVax has been demonstrated to confer mice and ferrets substantial protection against the SARS-CoV-2 challenge.…”
Section: Introductionmentioning
confidence: 98%
“…Needle‐free injectors for DNA vaccine delivery have been found to augment the immune response, possibly by enhancing the dispersion of injecting substances or increasing local inflammation 39 . Multiple approaches have been tried by various groups for vaccine delivery in the case of SARS‐CoV‐2 DNA vaccines like intramuscular, intradermal, oral, and electroporation techniques 28,31,32,40 . The use of the electroporation method for GX‐19 vaccine candidate delivery enhanced the antibody and T cell response in NHP's 31 …”
Section: Discussionmentioning
confidence: 99%
“…Another study in mice showed that the second dose of protein immunization, based on intradermal immunization with a novel inactivated coronavirus vaccine, protected mice from challenge infection with a mutant strain [11] . Based on the above analysis, we hypothesized that intradermal immunization might provide a new approach or strategy to solve the problem that anti-novel coronavirus antibodies are not durable or that variant strains can escape immune protection [18] , [19] , [20] . Because rhesus monkeys are similar to humans in anatomy and organ function and their biological characteristics are reliable, genetic background is relatively stable, adaptability is strong, and background information is abundant, they are widely used in pharmacology and toxicology studies [21] , [22] .…”
Section: Discussionmentioning
confidence: 99%